Angiomyxoma of the pelvis in women. Clinical cases - E. V. Slukhanchuk; A. G. Tyan; A. L. Bedzhanyan; L. M. Nechitaylo; O. V. Dolzhanskiy; T. N. Galyan (Акушерство, гинекология и репродукция)
Aggressive pelvic angiomyxoma belongs to one of the rare types of mesenchymal pelvic tumors found in premenopause patients. Currently, this pathology is mainly treated via surgical intervention. Alternatively, it may also be managed by using radiation or hormone therapy. The final diagnosis is usually established by histological examination of removed tumor, because biopsy analysis during examination may not always provide a high diagnostic value. This tumor type is able to relapse, even after 100 % surgically removed intervention. Immunohistochemistry examination reveals expression of progesterone and estrogen receptors. One of the hormone therapy options with good long-term effect is based on using gonadotropin-releasing hormone drugs. Taking into consideration slow tumor growth and hormonal sensitivity, one of the options for managing disease relapse is patient follow-up, especially in perimenopausal subjects. Single clinical cases have been published related to pelvic angiomyxoma so that it results in introducing individualized management for every certain patient, but unified therapeutic approaches have not been developed yet.